2016
DOI: 10.1002/anie.201604921
|View full text |Cite
|
Sign up to set email alerts
|

Formamides as Lewis Base Catalysts in SN Reactions—Efficient Transformation of Alcohols into Chlorides, Amines, and Ethers

Abstract: A simple formamide catalyst facilitates the efficient transformation of alcohols into alkyl chlorides with benzoyl chloride as the sole reagent. These nucleophilic substitutions proceed through iminium-activated alcohols as intermediates. The novel method, which can be even performed under solvent-free conditions, is distinguished by an excellent functional group tolerance, scalability (>100 g) and waste-balance (E-factor down to 2). Chiral substrates are converted with excellent levels of stereochemical inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 43 publications
(27 reference statements)
1
47
0
Order By: Relevance
“…The evaluation of other Lewis bases as catalysts for the transformation of model substrate 1 2 into 2 2 showed that any deviation from the original FPyr scaffold results in diminished catalytic activities, which are indicated by the yield of 2 2 (Table , entries 8–11; see also Scheme S4 in the Supporting Information). In fact, structural variations of the catalyst have a stronger deteriorative effect on the yield of 2 2 in comparison of TCT to BzCl, which is underpinned by the lower yield of 2 2 when DMF is applied (Table , entry 8). While methylformamide (MF) still furnishes 2 2 as major product, simple formamide (F) and dimethylacetamide (DMA) provide 2 2 only as a side product in traces (Table , entries 9–11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of other Lewis bases as catalysts for the transformation of model substrate 1 2 into 2 2 showed that any deviation from the original FPyr scaffold results in diminished catalytic activities, which are indicated by the yield of 2 2 (Table , entries 8–11; see also Scheme S4 in the Supporting Information). In fact, structural variations of the catalyst have a stronger deteriorative effect on the yield of 2 2 in comparison of TCT to BzCl, which is underpinned by the lower yield of 2 2 when DMF is applied (Table , entry 8). While methylformamide (MF) still furnishes 2 2 as major product, simple formamide (F) and dimethylacetamide (DMA) provide 2 2 only as a side product in traces (Table , entries 9–11).…”
Section: Resultsmentioning
confidence: 99%
“…Only when DMSO was applied as solvent the quantity of TCT could be lowered to 55 mol %. Recently, we discovered that formamides such as DMF and N ‐formylpyrrolidine (FPyr) are potent catalysts for the preparation of alkyl halides of type 2 from alcohols 1 with application of benzoyl chloride (BzCl) as sole reagent (Scheme C ) …”
Section: Introductionmentioning
confidence: 90%
“…[13] Compound (R)-2a could be obtained with 77 % yield and 95 % ee, as was established by GLC on a chiral phase. For the preparation of optically active (1-chloroethyl)benzene (2a) we relied on a recent report by Huy et al, who developed excellent reaction conditions for the stereoselective nucleophilic displacement of a secondary alcohol function to the respective chloro compound with inversion of configuration.…”
Section: Resultsmentioning
confidence: 74%
“…First of all, we followed a recently published protocol [13] for the stereospecific preparation of α-chloroethylbenzene (R)-2a from (S)- It′s preparation from optically active 1-phenylethanol (1) by twofold nucleophilic displacement via α-chloroor bromoethylbenzene (2a or 2b) was reported before in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation